Crystallographic, morphologic, electric, optical and magnetic analysis of the Dy2BiFeO6 novel material (2018)
We report structural analysis, surface morphology, magnetic ordering, dielectric response, optical feature and the electronic structure of the Dy2BiFeO6 novel complex perovskite. The samples were produced by the standard solid-state reaction recipe. Crystallographic analysis was performed by Rietveld refinement of experimental X-ray diffraction patterns. Results show that this material crystallizes in a perovskite with orthorhombic structure, which corresponds to the Pnma (#62) space group. From the Curie-Weiss fitting on the curve of susceptibility as a function of temperature we establish that the ordering corresponds to a paramagnetic-antiferromagnetic transition, with a Weiss temperature q=-18,5 K, which is compatible with the behavior of the inverse of susceptibility as a function of temperature, and a Néel temperatura TN=50,8 K. The Curie constant allowed for us to obtain an effective magnetic moment of 15,7 mB. The result of magnetization as a function of the applied field, measured at T=50 K, shows a magnetic hysteresis behavior that corroborate the magnetic ordering present for this temperature value. Measurements of the dielectric constant as a function of applied frequencies at room temperature give as a result a high relative dielectric constant (e=780). The reflectance curve as a function of the wavelength reveals the typical behavior of a double perovskite-like material and permits to obtain the energy gap 2,74 eV, which is characteristic of a semiconductor material.